1984
DOI: 10.1007/bf01870571
|View full text |Cite
|
Sign up to set email alerts
|

X-ray microanalysis of elements in frozen-hydrated sections of an electrogenic K+ transport system: The posterior midgut of tobacco hornworm (Manduca sexta) in vivo andin vitro

Abstract: The lepidopteran midgut is a model for the oxygen-dependent, electrogenic K+ transport found in both alimentary and sensory tissues of many economically important insects. Structural and biochemical evidence places the K+ pump on the portasome-studded apical plasma membrane which borders the extracellular goblet cavity. However, electrochemical evidence implies that the goblet cell K+ concentration is less than 50 mM. We used electron probe X-ray microanalysis of frozen-hydrated cryosections to measure the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(19 citation statements)
references
References 55 publications
1
17
0
1
Order By: Relevance
“…The K m for sodium was five times lower than that for potassium. The high affinity of KAAT1 for Na ϩ possibly allows the midgut cells to take up this ion even from the low concentrations (Ͻ5 mM) found in the lumen of M. sexta (17).…”
Section: Discussionmentioning
confidence: 99%
“…The K m for sodium was five times lower than that for potassium. The high affinity of KAAT1 for Na ϩ possibly allows the midgut cells to take up this ion even from the low concentrations (Ͻ5 mM) found in the lumen of M. sexta (17).…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps surprising given that the role of K þ , Cl À and Na þ ions is crucial for various essential functions in all cells, for maintenance of membrane polarization, pH stability inside and outside cells, and the transport of amino acids, carbohydrates, and HCO 3 À (Coddington and Chamberlin, 1999;Dow et al, 1984;Emery et al, 1998). Together with monovalent ions, heavy metals can reach the cell cytoplasm and be transported through epithelial cells to potential sites of deposition (Emery et al, 1998).…”
Section: Introductionmentioning
confidence: 95%
“…The fluid produced by the Malpighian tubules enters the hindgut where in terrestrial insects both ions and water can be selectively reabsorbed as required to maintain homeostasis (Coast et al, 1999). Plant-feeding insects need to cope with excess K + and Mg 2+ from their diet (Dow et al, 1984;Dow, 1987). It has been shown that adult locusts fed on grass have 1.6 times more K + in their hemolymph relative to starved locusts (Hoyle, 1954).…”
Section: Introductionmentioning
confidence: 99%